Accounting Information System on Multi Cooperative using Laravel Framework - Rafi Amalia Rahmanda; Tristiyanto .; Rizky Prabowo (Jurnal Komputasi, 2018)
A numerous multiple transaction will create difficulties in managing and obtaining information for cooperative. Lack of resource and which is expensive make cooperative difficult to build by themself. Thats why many cooperatives do not use software in managing finances.Accounting information system using SaaS (Software as a Service) model can be a solution of the problem. with the SaaS model, users do not need to buy the app but by just subscribing with the application directly can use the application. This paper describe how to develop accouting information system. Accounting information system already has accounting features according the accounting rules so that it will be easier to use andÂ  can fasilitate the cooperative in making financial statements.